2014
DOI: 10.1109/jbhi.2013.2284610
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Wake Classification With Actigraphy and Respiratory Effort Using Dynamic Warping

Abstract: This paper proposes the use of dynamic warping (DW) methods for improving automatic sleep and wake classification using actigraphy and respiratory effort. DW is an algorithm that finds an optimal nonlinear alignment between two series allowing scaling and shifting. It is widely used to quantify (dis)similarity between two series. To compare the respiratory effort between sleep and wake states by means of (dis)similarity, we constructed two novel features based on DW. For a given epoch of a respiratory effort r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 37 publications
1
68
1
Order By: Relevance
“…Although the addition of the proposed actigraphic feature DHAL improved the performance in sleep/wake detection for insomnia subjects, it is still inferior to that reported for healthy subjects (kappa value of 0.58 in [13]). As shown in Figure 2, the main challenge of actigraphy-based sleep/wake detection is to separate wakefulness with low activity and sleep in which a similar level of activity was found.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Although the addition of the proposed actigraphic feature DHAL improved the performance in sleep/wake detection for insomnia subjects, it is still inferior to that reported for healthy subjects (kappa value of 0.58 in [13]). As shown in Figure 2, the main challenge of actigraphy-based sleep/wake detection is to separate wakefulness with low activity and sleep in which a similar level of activity was found.…”
Section: Resultsmentioning
confidence: 72%
“…As shown in Figure 2, the main challenge of actigraphy-based sleep/wake detection is to separate wakefulness with low activity and sleep in which a similar level of activity was found. In fact, in order to improve the detection performance, many previous studies have shown the effectiveness of incorporating cardiac and respiratory features in addition to actigraphy for healthy subjects [11], [13], [16], [18]. These features exploit the relation between sleep stages and autonomic cardiorespiratory activity [19], [20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations